Isotopes of Carbon, Oxygen, and Hydrogen Ethanol in Fruit Wines - Oganesyants Lev A.; Panasyuk Alexander L.; Kuzmina Elena I.; Ganin Mikhail Yu. (Техника и технология пищевых производств)
Introduction. Like any other food product, alcoholic drinks are subject to falsification. The present research featured various methods of analysis that can be applied to control the quality and authenticity of wine production. In case of doubt, experts apply national and interstate standards, the most informative of which are based on the isotopic mass spectrometry principle. Fruit winemaking relies on beet or cane sugar. Researchers have to develop a method to identify the difference between conditionally exogenous alcohols, which are formed during fermentation, and real exogenous alcohols, introduced in the form of rectified ethyl alcohol of grain origin. In order to identify non-grape alcohol, experts measure the ratio of ethanol carbon isotopes in the wine. However, δ13C‰ alone is not sufficient to analyze fruit wines and other alcohol drinks. Ratios of 18O/16O and D/H isotopes can become an extra criterion to test the authenticity of fruit table wines. Study objects and methods. The mass spectrometric complex Delta V Advantage Thermo Fisher Scientific (USA) provided a precise analysis of 13C/12C, 18O/16O, D/H isotopes. Wine samples were prepared in laboratory conditions from six types of fruits: apples, pears, cherries, black currants, plums, and chokeberries. Apple wine was obtained from fermented wort; other samples were fermented from pulp. Fermentation temperature was 20 ± 2°C, while the yeast race was represented by Vishnyovaya 33. Results and discussion. In fruit wine production, grain ethanol is the most popular falsification tool: it increases alcohol content instead of sugar, and sometimes even without fermentation process. In this regard, the research focused on carbon, oxygen, and grain alcohols hydrogen isotope characteristics, as well as fruit wines, obtained as a result of technology violation. The fruit wine alcohol mixes developed from joint fermentation of fruit sugars and introduced sugary substances. Cane sugar, beet sugar, and corn glucose and fructose syrup were added to the wort or pulp to establish the isotopic characteristics of the mix. The rate of exogenous alcohol production was 5% by volume. Conclusion. The analysis of δ13C‰ indicator failed to detect introduced grain alcohol. The analysis of isotopes of all atoms in the ethanol molecule, namely carbon, oxygen, and hydrogen, proved to be much more effective. The introduction of sugary substances prior to or during fruit juice fermentation provided the required alcohol content. It also reduced the numerical value of δ18O‰ of ethanol, which makes it significantly different from that of fortified fruit wines obtained by introducing grain alcohol into fermented fruit juice. Thus, the δD‰ indicator can serve as an additional criterion in order to identify possible violations of technological process of fruit table wines production.